Analysis of the Chemical Content of Jamblang Bark (Syzygium cumin (L) Skeels) Using Gas Chromatography-Mass Spectrometry and Fourier Transform Infrared - Himyatul Hidayah; Ikhtianingsih, Windi; Surya Amal (Eureka Herba Indonesia, 2023)
Jamblang plant (Syzygium cumini (L.) Skeels) is a plant that has the potential as anticancer, antioxidant, anti-inflammatory, anti-allergic, antibacterial, hepatoprotective, gastroprotective, cardioprotective, antidiabetic, antihyperlipidemic. Jamblang plants contain chemical compounds of alkaloids, flavonoids, resins, tannins, and essential oils. This study aimed to identify the class of flavonoid compounds contained in jamblang leaf isolates using gas chromatography-mass spectrometry and Fourier transform infrared. The results of the identification of jamblang leaves showed that the isolate contained flavonoid compounds, the flavonol group, which also had 69 potential bioactive compounds.